Fizikalni eksperimenti 2: Zbirka laboratorijskih vaj - Repnik, Robert; Slavinec, Mitja; Klemenčič, Eva (University of Maribor Press, 2022)
Physical Experiments 2: Collection of Laboratory Exercises. Physical Experiments 2: a collection of laboratory exercises is intended for 2nd-year students of the Physics study program and the Subject Teacher study program, Orientation Physics at the Faculty of Natural Sciences and Mathematics in Maribor. Students perform laboratory exercises at the course Physical Experiments 2, which covers the field of electromagnetism and thermodynamics. This textbook has three chapters. The first chapter consists of obligatory laboratory exercises. Most of them connect different fields of physics or use new methods and techniques. The third chapter is devoted to the basics of preparation and analysis of graphs using the software.